Bacterial Alterations in Post-Cholecystectomy Patients Are Associated With Colorectal Cancer - Ren, Xinhua; Xu, Jun; Zhang, Yuanyuan; Chen, Guodong; Zhang, Yiwen; Huang, Qing; Liu, Yulan (Frontiers in Oncology, 2020)
Background: Although increasing evidences showed a correlation between cholecystectomy and the prevalence rate of colorectal cancer (CRC), and shed light on gut microbiota in colorectal pathogenesis, only a few studies focused on microbial alterations after cholecystectomy, and its sequent role in carcinogenesis and progression of CRC has not been reported. Thus, we aimed to investigate the bacterial alterations and tried to clarify their clinical significance. Methods: 104 subjects were enrolled and divided into post-cholecystectomy patients (PC, n=52) and healthy controls (HC, n=52). To investigate the bacterial role in carcinogenesis, PC patients were further separated into preCA_CRC (patients with precancerous lesions and/or CRC, n=9) and nonCA (patients without precancerous lesions and/or CRC, n=43) based on the histopathology. Qualified stool samples were collected for 16S rRNA gene sequencing to analyze the bacterial profile. Results: Our data showed noteworthy compositional and abundant alterations of bacterial microbiota in PC patients, characterized as Bacteroides ovatus, Prevotella copri, and Fusobacterium varium remarkably increased; Faecalibacterium prausnitzii, Roseburia faecis, and Bifidobacterium adolescentis significantly decreased. Additionally, the duration after cholecystectomy was the critical factor that affected bacterial composition. Machine learning-based analysis showed a pivotal role of Megamonas funiformis in discriminating PC from HC subjects and involving in the progression of CRC. Conclusions: The bacterial dysbiosis may associate with CRC in PC patients, and the duration after cholecystectomy was highlighted as an important factor. Altered bacterial microbiota was likely to play a pivotal role in related-disease in the long-term follow-up of PC patients.